2014
DOI: 10.1108/et-10-2012-0101
|View full text |Cite
|
Sign up to set email alerts
|

Personality, learning strategies, and academic performance

Abstract: Purpose -The purpose of this paper is to examine the relationships between personality traits, learning strategies and academic performance among undergraduate students in the post-Soviet transition country of Kazakhstan. Design/methodology/approach -The authors used a quantitative survey method to assess individual personality, learning strategies and academic motivations. Statistical software (SPSS) was used to conduct correlations, linear regressions and multiple regressions as a means of testing the hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 45 publications
2
17
0
1
Order By: Relevance
“…This resonates with the study of Moldasheva & Mahmood (2014), who revealed that collaborative learning is not usually practised among undergraduate students in Kazakhstan. It can be attributed to the sense of competition among the learners to achieve higher marks.…”
Section: Oc Activities Are Individual-orientedsupporting
confidence: 57%
“…This resonates with the study of Moldasheva & Mahmood (2014), who revealed that collaborative learning is not usually practised among undergraduate students in Kazakhstan. It can be attributed to the sense of competition among the learners to achieve higher marks.…”
Section: Oc Activities Are Individual-orientedsupporting
confidence: 57%
“…Many studies have been conducted to establish the relationship between ESL/EFL learning strategies, and the wide range of variables found in learners such as age or school year (e.g., Griffiths, 2003;Oxford & Ehrman, 1995;Riazi, 2007;Srisupha, 2012), English proficiency (e.g., Baker & Boonkit, 2004;Ghafournia, 2014;Murray, 2010), cultural background (e.g., Alhaisoni, 2012;Lengkanawati, 2004), motivation (e.g., Oxford & Nyikos, 1989), and personality traits (e.g., Kaufman et al, 2008;Moldasheva & Mahmood, 2014). Previous studies also found that more successful ESL/EFL learners tend to make more frequent use of learning strategies overall (e.g., Ghani, Mahfuz, Saad, & Yusoff, 2014;Akbari, 2003, Green & Oxford, 1995Murray, 2010;Wharton, 2000).…”
Section: Learning Strategy and Language Proficiencymentioning
confidence: 99%
“…Por otra parte se ha resaltado la relación entre la puesta en juego de determinadas estrategias y ciertas variables psicológicas, tales como rasgos de personalidad, motivación, ansiedad y flow, así como autorregulación afectiva, conductual y cognitiva, entre otras (Ben Eliyahu & Linnenbrink Garcia, 2015;Doménech Betoret, Gómez Artiga, & Lloret Segura, 2014;Kesici, Baloglu, & Deniz, 2011;Lee & Choi, 2013;Moldasheva & Mahmood, 2014;Sullivan, Eduljee, & Pinkham, 2012).…”
Section: Estrategias De Aprendizaje En Estudiantes Universitariosunclassified